Growth and Yield Performance of Cayenne Peppers in Ultisols - Angraini, Dila; Herison, Catur; Simarmata, Marulak; Ganefianti, Dwi Wahyuni; Sukisno; Rustikawati (BPFP Universitas Bengkulu, 2025)
Cayenne peppers (Capsicum annuum L.) are horticultural commodities with high economic value and increasing market demand, both for household consumption and large-scale processing industries. However, cayenne pepper productivity in Indonesia remains relatively low, partly due to the limited availability of fertile land. One potential solution to this problem is the utilization of marginal lands, including ultisols. Ultisols possess chemical characteristics that are less favorable for optimal plant growth, such as low pH, poor nutrient content, and high aluminum saturation. There fore, this study aimed to obtain information on cayenne pepper genotypes that can adapt well and produce optimally on ultisols. The research was conducted at the Experimental Garden of the Faculty of Agriculture, University of Bengkulu, from May to October 2023, using a Randomized Complete Block Design (RCBD) with three replications. Observed parameters included plant height, first dichotomous height, stem diameter, number of dichotomous points, total leaf area, shoot dry weight, stomatal density, days to first harvest, number of fruits per plant, fruit length and diameter, fruit weight per plant, and percentage of marketable fruits. Data were analyzed using ANOVA at a 5% significance level and followed by Duncan’s Multiple Range Test (DMRT) at the same level. The results indicated significant differences among genotypes in most growth and yield parameters. The genotypes ‘Iggo’ and ‘Lajang’ exhibited superior performance, with the highest dry biomass weight and the highest fruit weight per plant. These findings suggest that the ‘Iggo’ and ‘Lajang’ genotypes hold strong potential for cultivation on Ultisol soils to support sustainable national cayenne peppers production improvement.